Development and Implementation of Innovative Technologies That Ensure an Increase in The Extraction of Non-ferrous, Noble, Rare, Rare-Earth Metals - Kenzhaliyev, Bagdaulet Kenzhalievich; Arkad’yevich, Kvyatkovskiy Sergey; Anatolyevich, Trebukhov Sergey; Abdulvaliyev, Rinat Anvarbekovich; Koizhanova, Aigul; Tussupbayev, Nessipbay Kuandykovich; Gladyshev, Sergey Vladilenovich; Kassymova, Gulzhaina K. (Universitas Negeri Padang, 2022)
The article presents the most innovative technologies developed by Satbayev University,